2020
DOI: 10.1108/hff-07-2019-0549
|View full text |Cite
|
Sign up to set email alerts
|

Magneto hydrodynamic convection in a nanofluid saturated enclosure with porous fins

Abstract: Purpose This paper aims to numerically investigate the magnetohydrodynamic (MHD) convection heat transfer of nanofluid inside a differentially heated enclosure with various fin morphologies. Design/methodology/approach The fluid flow within the cavity was governed by N-S equations while it within porous medium was solved by the non-Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…Wind, geothermal and solar energies can be used to obtain such goal. Wind and solar energy are the most alternatives among these sources of energy (Wang et al , 2019; Zhu et al , 2020). Linear fresnel reflector (LFR) is a solar collector reflecting the rays onto a constant receiver standing along and upper the reflectors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wind, geothermal and solar energies can be used to obtain such goal. Wind and solar energy are the most alternatives among these sources of energy (Wang et al , 2019; Zhu et al , 2020). Linear fresnel reflector (LFR) is a solar collector reflecting the rays onto a constant receiver standing along and upper the reflectors.…”
Section: Introductionmentioning
confidence: 99%
“…They produced absorber fins with a carbon nanotubes device, and thicker fins can be installed in this system. Numerically, Wang et al (2019) analyzed the convection of nanomaterial in a heated container with different fin configuration. Their outcomes demonstrated that the estimation of mean Nu is increased by using more permeable fins with great permeability.…”
Section: Introductionmentioning
confidence: 99%
“…The efficient heat transfer enhancement techniques are the need of the hour for different practical applications such as solar collectors, process plants, textile and aerospace applications, processes involving polymeric composite manufacturing, etc Moharana, 2019a, Rashidi et al, 2019;Wang et al, 2019). The techniques used in reality for the purpose of transfer of heat are classified into two, namely active and passive methods (Mereu et al, 2013;Rashidi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The uses of corrugation in the wall (Mehta and Pati, 2018;Mousavi et al, 2020;Jaferian et al, 2019;Tiwari et al, 2017;Moharana, 2019b, 2019c), twisted tapes, ribs, baffles (Boruah et al, 2018;Boruah et al, 2019a) metallic porous media (Shamsabadi et al, 2019;Nebbali and Bouhadef, 2006;Bhowmick et al, 2020) and nanofluid (Rashidi et al, 2019;Boruah et al, 2019b;Darbari et al, 2020) are some of the passive heat transfer techniques for which external energy other than the pumping power is not needed. While the active techniques need external energy other than the pumping power to alter the flow field, and hence the heat transfer rate such as the application of electrical and magnetic fields (Rashid and Liang, 2020;Wang et al, 2019) for the flow of electrically conductive fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Their results report that the heat transfer increases with the increase in baffle length generally. Wang et al 25 studied the effect of horizontally applied uniform magnetic field on natural convection of CuO-water nanofluid in a square cavity in the presence of porous fins in different locations. They found that in case of large Darcy number and thermal conductivity ratio, the usage of more porous fins causes heat transfer rate to increase.…”
mentioning
confidence: 99%